Bamboo style exteriors, interiors, details - Guntli, Reto; Taschen, Angelika; Burkhardt, Christiane; Pautner, Norbert; Benguigui, Manuel (Icons, 2006)
Besides feeding pandas and making a yummy addition to many Asian dishes, bamboo is also used as a building material, both functional and decorative. This book captures the many uses of bamboo in houses throughout China, Japan and Indonesia.